Control effect of lanthanum against plant disease - 刘亚佳 王琰 王福宾 刘玉明 崔建宇 胡林 慕康国 (Journal of rare earths, 2008)
Effect of La on emergence, growth and development of Isatis indigotica Fort. and Festuca arundinacea seedlings was researched by pot experiments of inoculating Rhizoctonia solani and with the mixture ofRhizoctonia solani and Fusarium solani in disinfected soil after the seeds were soaked in the solution with different concentrations of La^3＋. The results indicated that infection rate decreased and there were significant disease controlling effects on seed rot, bud rot and root rot caused by pathogenic fungi when the seeds were soaked by La^3＋. Thus, the rates of emergence of Isatis indigotica Fort. and turfgrass Festuca arundinacea were increased, When La^3＋ concentration was in a proper range, the growth and development of plant seed/ings were promoted. Spraying La on rice plants showed a significant controling effect on Rhizoctonia solani. Furthermore, the EC50 of La^3＋performed 128.7 and 128.1 mg/L at 1 and 7 d after spraying La in rice plants, respectively. The EC50 of La^3＋ performed in vivo （in rice plant） was lower than that in vitro （171.9 mg/L）.